Endogenous risk in a DSGE model with capital-constrained financial intermediaries - Hans Dewachter; Raf Wouters (National Bank of Belgium, 2012)
This paper proposes a perturbation-based approach to implement the idea of endogenous financial risk in a standard DSGE macro-model. Recent papers, such as Mendoza (2010), Brunnermeier and Sannikov (2012) and He and Krishnamurthy (2012), that have stimulated the research field on endogenous risk in a macroeconomic context, are based on sophisticated solution methods that are not easily applicable in larger models. We propose an approximation method that allows us to capture some of the basic insights of this literature in a standard macro-model. We are able to identify an important risk-channel that derives from the risk aversion of constrained intermediaries and that contributes significantly to the overall financial and macro volatility. With this procedure, we obtain a consistent and computationally-efficient modelling device that can be used for integrating financial stability concerns within the traditional monetary policy analysis.
Keywords: 330; Finanzintermediation; Risikopräferenz; Finanzkrise; Dynamisches Gleichgewicht